Peningkatan Kemampuan Gross Motor Skill Terhadap Anak-Anak di Kecamatan Muara Gembong Kabupaten Bekasi Dengan Menggunakan Media GECE (Gerak Cepat) - Juli Candra; Ery Teguh Prasetyo; Gede Aditya Pratama; Prio Kustanto; Eskar Tri Denatara; Jantarda Mauli Hutagalung; Gustinus Putera Tin; Rezal Wijaya; Dewi Sinta; Adi Yoga Suryana (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
The gross motor skills of children in Muara Gembong sub-district, Bekasi district, are not in accordance with growth and development because the educational learning process due to the impact of Covid 19 is carried out online, so that it has an impact on decreasing Gross Motor Skills and decreasing students' physical fitness. The purpose of community service activities is to improve gross motor skills by using GeCe (Fast Motion) media, a tool used to measure speed, agility, flexibility. The method used is the lecture method for tool socialization activities, training on the use of tools, and mentoring. The results of the activity show that the application of the GeCe tool is able to improve the Gross Motor Skill of children in the Muara Gembong area. In conclusion, community service activities have a positive impact on the community in Muara Gembong District, especially helping in developing and improving Gross Motor Skills. The limitation in this activity is the relatively short time so that the objectives of the activity cannot be optimally achieved. Suggestions For the implementation of community service in the future it can be carried out in a better and sustainable manner because in the Muara gembong area there are still a lot of activities that need to be carried out in developing community activities in increasing human resources man.